Taxonomical Description, Nativity and Endemism with Particular Reference to Threatened Ethnomedicinal Plants of Almora District of Western Himalaya - Tewar, Priti Kumari, Girish C. Joshi, Lalit M. (Journal of Phytology, 2015)
Out of 187 ethno-medicinal plants of Almora district (Kumari et. al. 2011), identifications, distribution, nativity and endemic/near endemic of 21 threatened ethno-medicinal plant species were studied. These 21 species of ethno medicinal plants belonging to 16 families were recorded. Of these, 2 species were trees, 1 shrub, 16 herbs and 2 climbers. The families Taxaceae, Ranunculaceae, Berberadaceae, Euphorbiaceae, Saxifragaceae,Verbenaceae,Bignonoaceae, Celastraceae, Costaceae, Dioscoreaceae, Hypoxidaceae, Valerianaceae and Gentianaceae having single species,Â  Lamiaceae, having two species and Orchidaceae, Liliaceae having three species were identified.